2020
DOI: 10.1111/dth.14283
|View full text |Cite
|
Sign up to set email alerts
|

A new clinical and dermoscopic monitoring of infantile hemangiomas treated with oral propranolol

Abstract: Oral propranolol (OP) demonstrated high efficacy and safety profile for treatment of critical infantile hemangiomas (IHs). Our aim was to assess the morphologic changes of IHs with standard and high-resolution video dermoscopy (HRVD) from baseline to 18 months either in presence or absence of OP therapy; to investigate if extended anamnestic perinatal data and clinical-dermoscopic characteristics of the IHs can correlate with therapeutic outcome. We enrolled 94 patients (112 IHs): 58 were treated with OP, 35 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…7,11 Studies have reported that more than half of untreated IH has not completely involution, and there residual Sequelae lesions in IH after involution. 8,9,12 These Sequelae lesions include telangiectasia, skin atrophy, excess skin, scars or fibrofatty tissue. This retrospective study showed that 39.5% of superficial IH in the observation group did not completely involution.…”
Section: Discussionmentioning
confidence: 99%
“…7,11 Studies have reported that more than half of untreated IH has not completely involution, and there residual Sequelae lesions in IH after involution. 8,9,12 These Sequelae lesions include telangiectasia, skin atrophy, excess skin, scars or fibrofatty tissue. This retrospective study showed that 39.5% of superficial IH in the observation group did not completely involution.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new non-invasive imaging devices that provide high-resolution skin images, such as high-resolution videodermoscopy (HRVD) [14][15][16], high-frequency ultrasound [15], and line-field confocal optical coherence tomography (LC-OCT) [15,[17][18][19], have been successfully employed in vascular skin lesions [14,15,17,18], orienting the diagnostic suspect in atypical/featureless cases.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The histopathological examination is the gold standard for differential diagnosis with Kaposi sarcoma, [4][5][6] but non-invasive high-resolution imaging techniques are today available. [7][8][9][10] A 78-year-old patient presented for an ulcerative lesion on the right pre-tibial lesion occurred 10 days before in the context of a pigmented greyish area with clear-cut margins persistent since about 9 years, which appeared greyish to erythematous and soft at palpation; imprinted oedema was detectable in the distal portion (Figure 1c). The patient experienced a trauma at the right leg about 10 years before with followed by ulceration and erysipeloid infection.…”
mentioning
confidence: 99%
“…The patient experienced a trauma at the right leg about 10 years before with followed by ulceration and erysipeloid infection. A noninvasive mapping combining high-resolution videodermoscopy (HRVD) 7 [HS600 Horus (Adamo S.r.l. )], 7 high-frequency ultrasound 8 (HFUS) 24-30 MHz [MyLab™X8 (Esaote)] and line-field confocal optical coherence tomography (LC-OCT) [Deeplive® (Damae)] 9,10 was realized at different lesional points (Figure 1, white circles).…”
mentioning
confidence: 99%
See 1 more Smart Citation